Unevenly distributed LED light produces distinct behavioral preferences and production performance of broilers - Pan, Chenghao; Lu, Minsi; Zhang, Yingping; Yu, Yue; Liu, Qiuyan; Yang, Yefeng; Pan, Jinming (International Journal of Agricultural and Biological Engineering, 2019)
LED has shown great advantages in poultry husbandry. This study focused on the behavioral preferences and production performance of chicken broilers reared under unevenly distributed yellow LED light. Four pens were divided into two groups adopting respective maximum light intensities (MLIs, 60 lx and 30 lx). Because of different distances from the installation position of the LED pipe, each pen was distributed with unevenly distributed light. Each pen consisted of four subzones indicated by their light intensities-high intensity (HI), medium intensity (MI), low intensity (LI) and weak intensity (WI). Four subzones were the same size and provided with a feeder and a drinker, respectively. The broilers moved freely across the four subzones. No significant differences in body weight (BW), uniformity of final BW and feed conversion ratio (FCR) were observed between the two experimental groups. However, greater feed intake and water intake were found in HI than those in other subzones. The drinking preference changed with age for four subzones and was more likely to appear at the later stage, despite substantial fluctuations within the replicates. The feeding preference was more constant than the drinking preference and appeared mainly at the early and middle stages of this study. These findings could provide implications for broiler production reared under unevenly distributed LED light condition.Keywords: LED, unevenly distributed light, behavioral preference, broiler production performance, light intensity, artificial lighting, animal welfareDOI: 10.25165/j.ijabe.20191202.4689Citation: Pan C H, Lu M S, Zhang Y P, Yu Y, Lu Q Y, Yang Y F, et al. Unevenly distributed LED light produces distinct behavioral preferences and production performance of broilers. Int J Agric & Biol Eng, 2019; 12(2): 49–53.